A terminologia das Feiras de negócios: análise das variantes linguísticas - Godoy, Ariane Dutra Fante [UNESP]; Babini, Maurizio [UNESP] (My University, 2013)
The trade fair industry has great relevance in the national and international economic environment and it is constantly expanding. The general objective of this work is to analyze the main linguistic variants found in the trade fair terminological set. Our research is based on the theories of Cabré (1993, 1999), Barros (2004), Krieger & Finatto (2004), Alves (2007), Barbosa (2009), Dubuc (1985), Berber Sardinha (2004), Babini (2006) and Faulstich (1998, 2001). For this work we constitute two corpora of specialized texts, one for English language and another for Portuguese language. Successively we performed a collection of terms using software for corpora processing. These terms were organized into two notional systems, one in English and another in Portuguese. Then we analyzed the main types of variants found in our terminological set. Among them, those who had higher productivity are the lexical variants, followed by graphical, morphological and syntactic variants.

O Setor feirístico tem grande relevância no cenário econômico nacional e internacional e está em constante expansão. O objetivo geral deste trabalho é analisar as principais variantes linguísticas encontradas no conjunto terminológico das feiras de negócios. Nossa pesquisa está baseada nas teorias de Cabré (1993, 1999), Barros (2004), Krieger & Finatto (2004), Alves (2007), Barbosa (2009), Dubuc (1985), Berber Sardinha (2004), Babini (2006) e Faulstich (1998, 2001). Para efetuarmos esse trabalho constituímos dois corpora de textos especializados, um para a língua inglesa e outro para a língua portuguesa. Sucessivamente, procedemos à coleta dos termos por meio de software para processamento de corpora e esses termos foram organizados em dois sistemas nocionais, um para a língua portuguesa e outro para a língua inglesa. Em seguida, procedemos à análise dos principais tipos de variantes encontradas em nosso conjunto terminológico. Dentre elas, as que tiveram maior produtividade são as variantes lexicais, seguidas das variantes gráficas, morfológicas e sintáticas.
Terminology of trade fairs: analysis of linguistic variants
Keywords: Feiras; Setor feirístico; glossário bilíngue; glossário terminológico; trade fair; terminology; linguistic variation; terminological variant